ENHANCING DIGITAL COMPETENCIES OF STUDENTS AT MUHAMMADIYAH AL MUJAHIDEEN ISLAMIC JUNIOR HIGH SCHOOL THROUGH PYTHON-BASED CODING INSTRUCTION - Darmanto, Darmanto; Pratama, Ridho Haikal; Hazar, Siti; Rajunaidi, Rajunaidi; Hafin, Aqid Fahri; Ridwan, Muhammad; Bidinnika, Muhammad Kunta; Murinto, Murinto; Yuliansyah, Herman (Jurnal Pengabdian Masyarakat Sabangka, 2025)
In the digital era, programming has become an essential skill for students. This community service activity aimed to introduce Python-based coding instruction to students at Muhammadiyah Al Mujahideen Islamic Junior High School, combining digital literacy with Islamic character development. The activity followed a three-stage model: planning, implementation, and evaluation. During the two-day training, students were taught basic Python concepts such as syntax, variables, and data types using the W3Schools platform. Tasks were designed to evaluate their understanding, including coding exercises to calculate the area of basic geometric shapes. Results showed high enthusiasm and full task completion by all 20 participants, indicating that junior high school students can grasp foundational programming concepts when supported by clear instruction and engaging materials. This program demonstrates the potential of integrating Python into early education to support national education goals and foster future-ready, ethically grounded digital citizens.